Higher PLIN5 but not PLIN3 content in isolated skeletal muscle mitochondria following acute in vivo contraction in rat hindlimb. Issue 10 (15th October 2014) - Ramos, Sofhia V.; MacPherson, Rebecca E. K.; Turnbull, Patrick C.; Bott, Kirsten N.; LeBlanc, Paul; Ward, Wendy E.; Peters, Sandra J.
Abstract Contraction‐mediated lipolysis increases the association of lipid droplets and mitochondria, indicating an important role in the passage of fatty acids from lipid droplets to mitochondria in skeletal muscle. PLIN3 and PLIN5 are of particular interest to the lipid droplet–mitochondria interaction because PLIN3 is able to move about within cells and PLIN5 associates with skeletal muscle mitochondria. This study primarily investigated: 1) if PLIN3 is detected in skeletal muscle mitochondrial fraction; and 2) if mitochondrial protein content of PLIN3 and/or PLIN5 changes following stimulated contraction. A secondary aim was to determine if PLIN3 and PLIN5 associate and whether this changes following contraction. Male Long Evans rats (n = 21; age, 52 days; weight = 317 ± 6 g) underwent 30 min of hindlimb stimulation (10 msec impulses, 100 Hz/3 sec at 10–20 V; train duration 100 msec). Contraction induced a 50% reduction in intramuscular lipid content measured by oil red‐O staining of red gastrocnemius muscle. Mitochondria were isolated from red gastrocnemius muscle by differential centrifugation and proteins were detected by western blotting. Mitochondrial PLIN5 content was 1.6‐fold higher following 30 min of contraction and PLIN3 content was detected in the mitochondrial fraction, and unchanged following contraction. An association between PLIN3 and PLIN5 was observed and remained unaltered following contraction. PLIN5 may play a role in mitochondria during lipolysis, which is consistent with a role in facilitating/regulating mitochondrial fatty acid oxidation. PLIN3 and PLIN5 may be working together on the lipid droplet and mitochondria during contraction‐induced lipolysis.